Exploring the Nature of Teachers’ Math-Gender Stereotypes: The Math-Gender Misconception Questionnaire - Dersch, Anna-Sophia; Heyder, Anke; Eitel, Alexander (Frontiers in Psychology, 2022)
Stereotypes of girls having weaker mathematical abilities than boys (math-gender stereotypes) are one factor reducing women’s representation in mathematics. Teachers, as powerful socializers, often hold math-gender stereotypes. Reducing math-gender stereotypes in (student) teachers thus may foster women’s representation in mathematics. Yet knowing the stereotypes’ underlying assumptions is crucial to reducing it. Do math-gender stereotypes reflect elaborate, disproven theories about gender differences in math, meaning math-gender misconceptions? And if so, which math-gender misconceptions are behind math-gender stereotypes? This is the focus of the present research. The relevant literature implies the existence of three distinct misconceptions: (1) empathizing-systemizing (“As girls think rather empathically and boys think rather systematically, boys are on average more talented in math than girls”), (2) girls’ compensation (“To achieve equally good grades in mathematics, boys have to make less effort because they are more talented than girls are”), and (3) girls’ non-compensability (“Despite their on average stronger effort, girls are normally less proficient in math than boys”). We assessed these misconceptions in a student teacher sample (N = 303) using our newly developed Math-Gender Misconceptions Questionnaire. Our results offer support for the expected three-factor structure of math-gender misconceptions. All three math-gender misconceptions showed good to acceptable scale reliabilities. On average, preservice teachers did not hold (strong) math-gender misconceptions. But a subgroup of 48.2% of preservice teachers held at least one of the three misconceptions. The empathizing-systemizing misconception was the most prevalent (32.0%) among the three misconceptions. Descriptively, endorsing the math-gender stereotype correlated most strongly with the empathizing-systemizing (r = 0.43) and the girls’ compensation misconception (r = 0.44). This may indicate that especially these two misconceptions partly underlie math-gender stereotypes. As a consequence, refutation instructions designed to reduce these misconceptions may be a promising method to weaken math-gender stereotypes. Further research is needed to investigate to what degree reducing the present misconceptions is related to reducing math-gender stereotypes. Hence, this study is the first one of a planned series of studies on the relation between math-gender misconceptions and math-gender stereotypes.